Application of Electrostatic Solvent Extraction for Process Metallurgy - Ichlas, Zela Tanlega (Curtin University, 2022)
The thesis is aimed to investigate the behaviours of smaller droplets under more vigorous electrostatic field conditions than those previously studied. New insights into the behaviours of these smaller droplets have been gained, and the conditions to allow high mass transfer rates and fast phase disengagement are determined. This work would be valuable to optimise the design of an electrostatic solvent extraction (ESX) column and contribute toward a commercial application of ESX for process metallurgy.